Surat At-Tur As A Source Of Qur’anic Guidance And Arabic Language Enrichment: A Thematic Educational Study/ سورة الطور كمصدر للهداية القرآنية وتعزيز اللغة العربية: دراسة تربوية موضوعية - Abdeldayem, Walied Ali Mohammad; Bostan, Al-Mutawalli Ali Al-Shahat (Ijaz Arabi Journal of Arabic Learning, 2025)
The Holy Qur’an was revealed as a guide and a beacon for all humanity. Each sura offers moral and spiritual direction through reflection and contemplation. This study contributes to Arabic language teaching by showing how Surat At-Tur's vocabulary, structure, and rhetorical features can enhance learners’ proficiency in classical Arabic. The study focuses on the practical lessons of Surat At-Tur, emphasizing its role in guiding belief, behavior, worship, and ethics—particularly in response to modern atheistic and anti-Islamic narratives disguised as progress and civilization. It also highlights the sura’s relevance to contemporary issues facing Muslims in Western and non-Muslim societies, including the importance of family cohesion and moral resilience. The research identifies educational insights that extend beyond religious instruction using inductive, analytical, and deductive methods. It presents Surat At-Tur as a source of holistic guidance that speaks to personal development and societal well-being. In conclusion, the sura offers valuable spiritual formation and language education content. Its enduring relevance lies in its ability to address modern challenges while deepening engagement with Qur’anic Arabic, making it a beneficial resource for educators, students, and community leaders.